Capital Theory and Developmental Planning - Findlay, Ronald (Review of Economic Studies, 1962)
Journal Article Capital Theory and Developmental Planning Get access Ronald Findlay Ronald Findlay Rangoon Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 2, February 1962, Pages 85–98, https://doi.org/10.2307/2295816 Published: 01 February 1962